2018
DOI: 10.1016/j.msea.2018.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behavior and microstructure evolution of a quenched and partitioned steel during drop weight impact and punch testing

Abstract: In this work, a Fe-0.25C-3.0Mn-1.5Si-0.023Al-0.015Cr (wt. %) steel was subjected to the Q&P treatment, and its mechanical behavior and microstructure evolution during drop weight impact testing and quasi-static punch testing were thoroughly analyzed. It is shown that the 1 mm thick Q&P steel sheet can withstand 110 J impact energy without any (micro) cracking, which is well above the impact resistance of DP 1180 steel. The local true plastic strain can reach 53.4% in biaxial stretching showing excellent formab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…It can be concluded that the impact crashworthiness of the 1 mm thick 304 SS is 130 J. This value is higher than that of the quenching and partitioning (Q&P) steel showing the impact resistance of 110 J in our previous publication [25]. However, in another report by J.A.…”
Section: Uniaxial Tensile Properties Of the Studied 304 Ssmentioning
confidence: 54%
“…It can be concluded that the impact crashworthiness of the 1 mm thick 304 SS is 130 J. This value is higher than that of the quenching and partitioning (Q&P) steel showing the impact resistance of 110 J in our previous publication [25]. However, in another report by J.A.…”
Section: Uniaxial Tensile Properties Of the Studied 304 Ssmentioning
confidence: 54%
“…Less retained austenite in the EBSD method is due to a limited resolution of the analysis. Hence, the smallest blocky retained austenite grains and thin layers of this phase cannot be revealed [29,30,31]. These microstructural components can be detected using the X-ray diffraction [15,25].…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, the electron backscatter diffraction (EBSD) technique can be successfully applied. The EBSD method is useful for determining a volume fraction of microstructural constituents: bainite, ferrite, and austenite [29,30,31,32,33]. Petrov et al [30] used this method to determine an amount of retained austenite in a TRIP-assisted steel deformed to 10%.…”
Section: Introductionmentioning
confidence: 99%
“…3. Schematic presentation of a cross-sectioned sample [53]. The area marked by white square refers to the region selected for EBSD and TEM characterization.…”
Section: Mechanical Property Characterizationmentioning
confidence: 99%